Faktor yang Mempengaruhi Pengembangan Klaster Batik Laweyan-Surakarta Menuju Ekonomi Lokal Berkelanjutan - Abdul Muin (Jurnal Wilayah dan Lingkungan, 2013)
Condition of economics of Kampung Batik Laweyan Surakarta as Klaster economics still have not good enough yet compared to a period of its glory in 1970 though there are improvements since 2004. Now it is having much attention of public and government. Even many experts have commented the existence that this area is so important and competent to be developed. To be able to develop cluster in order to reach the sustainable economics process, it is important to know the primary factor that influencing it. The factors can be in the form of condition and activity which is its constraint and potency. There are factors known in general, but also special factor at Kampung Batik Laweyan, and  to know it hence done by this research. In determining variable which will be checked hence done by taking factor from theory that expressed by some expert (positivistic approach) allied by variable in result of research before (rationalistic approach).  Research is done with quantitative method with looking for as many as possible opinion of the entrepreneur and conclude it in general as image of about factor that becomes perception of all entrepreneur the in the area. Out of 25 variables questioned to the entrepreneur, with factor analysis yielded, there are 7 (seven) factors which very influential to the development of Batik Laweyan cluster towards having sustainable local economics including entrepreneur performance factor (13,79%), support from local government (13,27%), resource exploiting (11,97%), company management (11,59%), social characteristic (9,62%), strength of local business (9,14%) and non local purchasing (5,30%). Entrepreneur performance factor property of main variable in the form of action with trust and also regeneration.  It indicates the most important to be considered is the entrepreneur.